URGENSI PERLINDUNGAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL PADA PLATFORM MEDIA SOSIAL - Aksar, Aksar; Fatwa, Indra; Farras, Aqil; Aziz, Abdul (LPPM, Universitas Muhammadiyah Riau, 2025)
The rapid development of digital technology has significantly transformed how individuals and institutions distribute and access intellectual works. Social media platforms have become primary spaces for the dissemination of creative content, but they also present new challenges in the protection of Intellectual Property Rights (IPR). The increasing incidents of violations such as plagiarism, digital piracy, and unauthorized distribution highlight gaps in the current legal protection systems. This study aims to examine the urgency of establishing and enforcing adaptive IPR regulations that align with the dynamics of social media in the digital era. Using a normative juridical approach and literature analysis, the research finds that existing regulations are insufficient to address the complexity of IPR infringements in digital environments. Therefore, legal policy reform, cross-sector collaboration, and improved public digital literacy are essential to building a fair and equitable social media ecosystem for content creators.